Análise fractal do osso mandibular e a ocorrência de osteorradionecrose: um estudo transversal com grupo controle - Natália Santos Barcelos (2023)
Fractal analysis of mandibular bone and occurrence of osteoradionecrosis: a cross-sectional study with control group Radiotherapy (RT) is widely used in the treatment of head and neck cancer. Osteoradionecrosis (ORN) is one of the most severe complication of this therapeutic modality. All patients treated with RT are considered at high risk for the development of ORN, due to the lack of predictive factors for ORN, the morbidity, and the unpredictable response to treatment. Fractal analysis is used to describe the complexity of a structure and to assess abnormalities and the severity of bone architecture disorders. However, few studies have used fractal analysis to assess the bone structure of patients undergoing RT in head and neck region. Therefore, the aim of this study was to evaluate the FD and lacunarity of the mandibular bone in individuals who received radiation therapy for HNC, comparing those who had developed ORN to those who had not developed ORN (control group). The study was approved by the Research Ethics Committee of the Universidade Federal de Minas Gerais (certificate number: 30560820.9.0000.5149). This is a cross-sectional study with a control group and thirty-four patients were included and divided into case group (with ORN, n=17) and control group (without ORN, n=17). One digital panoramic radiograph acquired after the end of RT was evaluated for each patient. FD and lacunarity of the mandibular bone were determined using ImageJ software. Bivariate statistics was done, as well as ROC curve analysis. Significance was stablished at p< 0.05. The mean FD and lacunarity values were not significantly different between the groups. The area under the curve for FD and lacunarity were 0.576 and 0.626, respectively. The cut-off point found for FD was ≤1.1736 and >0.4155 for lacunarity, allowing us to correctly classify cases and controls. Most participants in the case group (92.9%) had a FD >1.1736 and all participants in the control group had a FD ≤ 1.1736 (p < 0.001). For lacunarity, most individuals in the case group (71.4%) had a value >0.4155 and all participants in the control group had a value ≤0.4155 (p <0.001). Conclusion: The cut-off values of FD and lacunarity of mandibular bone, assessed on panoramic radiographs, differ between patients with and without ORN.